Strategi Mengajarkan Keterampilan Hidup Sehari-Hari Untuk Anak dan Remaja Dengan Retardasi Mental: Sebuah Review Literatur: LITERATUR REVIEW - sholihah, wiyanti maratus (Universitas Nusantara PGRI Kediri, 2021)
Abstract Educational programs for students with mental retardation emphasize the preparation of students to live independently after finishing school. One educational strategy for children and adolescents with mental retardation is to teach daily life skills. The purpose of this study is to conduct a literature review on strategies to teach daily life skills to children and adolescents with mental retardation. Literature searches were carried out on seven databases, namely ERIC, SpringerLink, ScienceDirect, SAGE, JSTOR, Emerald Insight and Google Schoolar. The keywords used in this search are